Vitamin D-Resistant Rickets and Cinacalcet—One More Favorable Experience - Nicolescu, Ramona C.; Lombet, Jacques; Cavalier, Etienne (Frontiers in Pediatrics, 2018)
Hereditary vitamin D-resistant rickets (HVDRR) is an autosomal recessive disorder characterized by early onset of severe rickets, with a complete triad of clinical, biochemical and skeletal abnormalities. Homogeneous or heterogeneous mutations in the vitamin D receptor (VDR) gene leading to complete or partial target organ resistance to the action of 1α, 25-dihydroxyvitamin D3 (the active form of vitamin D) are responsible for HVDRR. Theoretically the therapeutic goal is to overcome this tissue resistance, and to normalize calcium and phosphate homeostasis. Practically, the treatment could be oriented to correct the secondary hyperparathyroidism to avoid long-term negative impact on bone health. The conventional therapeutic strategy (high-dose calcium plus active vitamin D metabolites) gives variable responses in magnitude and duration. We report a case of HVDRR with mutant VDR, neonatal alopecia, and a severe clinical phenotype diagnosed at the age of thirty months and then showing unsatisfactory response to traditional therapy. The short-term responsiveness to cinacalcet was encouraging, with adequate correction of phosphate-calcium homeostasis and significant improvement of clinical and radiological status at six months of treatment.